Considerations of constructing quality, health and safety management system for agricultural products sold via e-commerce - Ma, Chen; Wang, Dongyang; Hu, Zhiquan; Li, Zhi (International Journal of Agricultural and Biological Engineering, 2018)
The continual development of internet technology and its extensive applications in the business domain have enabled the development of e-commerce in relation to agricultural products. However, this development is facing some “pain points.” While middle-class consumers are displaying ever-increasing demand for high-quality agricultural products via the e-commerce environment, the quality and safety of agricultural products under this environment cannot be guaranteed. Therefore, to strengthen the evaluation of the technical level of agricultural products quality, health and safety supervision via e-commerce, understand the problems in the regulatory techniques of e-commerce of agricultural products in China, increase the agricultural product quality, health and safety supervision via e-commerce are of great importance to satisfy the growing consumer demand for e-commerce in agricultural products. Based on the comparative analysis of the evaluation methods and the establishment methods of evaluation index system, this research innovatively established quality, health and safety index system for agricultural products sold via e-commerce, which included 6 first-level and 13 second-level indices. The establishment of the index system provides a method for quality, health and safety regulation for agricultural products via e-commerce. In addition, based on the theory of Hazard Analysis and Critical Control Point (HACCP), this paper combed the key links and control points of quality and safety for agricultural products via e-commerce and provided an evaluation basis for the quality and safety management system of agricultural products under the e-commerce environment. Finally, in view of the shortcomings of the current quality and safety for agricultural products via e-commerce, and the development trend of the future electronic commerce of agricultural products, the paper put forward the countermeasures and suggestions. Keywords: agricultural products, e-commerce, quality and safety, supervision, management system DOI: 10.25165/j.ijabe.20181101.3005 Citation: Ma C, Wang D Y, Hu Z Q, Li Z. Considerations of constructing quality, health and safety management system for agricultural products sold via e-commerce. Int J Agric & Biol Eng, 2018; 11(1): 31–39.